The Role of Family and Community in Preventing Stunting in Toddlers - Eduardo Crisogono Gaio; Joaquim Pinto; Carlos Boavida Tilman; Virgilio Soares; Ermelinda da Costa Monteiro; Antonio Ximenes (Westscience Press, 2025)
Stunting remains a critical public health problem that affects children’s physical growth, cognitive development, and long-term human capital, particularly in low- and middle-income countries. Increasing evidence suggests that stunting is not solely a nutritional issue but a multidimensional condition influenced by family practices and community environments. This study aims to systematically review the role of family and community in preventing stunting among toddlers. A systematic literature review was conducted using ten peer-reviewed articles indexed in the Scopus database. The review followed a structured search, selection, and thematic synthesis process to identify key family- and community-level determinants and interventions associated with stunting prevention. The findings indicate that family-related factors—such as parental education, caregiving practices, household food security, and health-seeking behavior—play a central role in reducing stunting risk. At the community level, supportive health services, nutrition education programs, sanitation infrastructure, and social support networks significantly strengthen family capacity and promote sustainable behavior change. Importantly, the review highlights that integrated family–community approaches are more effective than isolated interventions, as they align household practices with enabling community environments. This study contributes to the literature by reinforcing the importance of multi-level, socially grounded strategies for stunting prevention and provides evidence-based insights for policymakers and practitioners seeking to design holistic and sustainable child nutrition interventions.⁠